An anticlockwise P–T–t path at high‐pressure, high‐temperature conditions for a migmatitic gneiss from the island of Fjørtoft, Western Gneiss Region, Norway, indicates two burial events during the Caledonian orogeny. (19th March 2019) - Liu, Penglei; Massonne, Hans‐Joachim
Abstract: The Blåhø Nappe on the island of Fjørtoft, which represents an isolated portion of the Seve Nappe Complex in the Western Gneiss Region, Norway, has been suggested to have experienced two deep burial cycles during the Caledonian orogeny. However, evidence on this multiple burial process by the derivation of a pressure–temperature–time ( P–T–t ) path has never been given in the literature. In this study, the 'diamondiferous' kyanite–garnet gneiss from the Blåhø Nappe on Fjørtoft was revisited to determine if such a process was correct. Two types of garnet, porphyroblastic garnet‐1 and fine‐grained garnet‐2, were recognized in the gneiss. The core of garnet‐1 is poor in Ca and documents P–T conditions of 1.2–1.3 GPa at c . 880°C based on pseudosection modelling. The inner rims of garnet‐1 and the core of garnet‐2 are both richer in Ca, recording P–T conditions of 1.35–1.45 GPa and 770–820°C. Application of conventional geothermobarometry on the outer rim of garnet‐1 and the rim of garnet‐2 yielded retrograde P–T conditions of 0.75–0.90 GPa and 610–685°C. These estimates define an anticlockwise P–T path at pressures below 1.5 GPa. Accessory monazite was dated with the electron microscope. Relicts of detrital monazite in the gneiss point to Sveconorwegian and possibly also Cryogenian provenance for the detritus of the sedimentary protolith. Metamorphic monazite in the gneiss records a wide age range from 460 to 380 Ma, with a peak c . 435 Ma and a shoulder at 395 Ma. These data suggest that the original (Ediacaran?) Baltica margin sediment (gneiss protolith) was transported to the base of an overlying plate during the early Caledonian (pre‐Scandian) orogeny. A long residence time of the metasedimentary rock at this base caused its heating to 880°C and homogenization of the early garnet chemistry. The late Caledonian (Scandian) collision between Baltica and Laurentia led to further burial, during which the studied gneiss was close to the former surface of the downgoing continental plate and, thus, cooled. The reconstructed P–T–t path confirms the multiple burial history of the Blåhø Nappe but contradicts previous ideas of deep burial of the Fjørtoft gneiss to more than 100 km.